Environmental Performance: Role of Green Purchasing, Green Supply Chain Integration, and Management Commitment with Strategic Planning as Mediator - Burhanuddin Burhanuddin; Mariana Tenreng; Syamsiah Badruddin; Imran Ismail (International Journal of Supply Chain Management, 2019)
The main prime objective of this paper is to examine the impact of management commitment, green supply chain, and green purchasing on strategic planning and environmental performance. Moreover, mediating role of strategic planning between management commitment and environmental performance is explored in the current study as well. This study employed survey as a data gathering method and designed a structured questionnaire keeping in view the research objectives. At the data analysis stage, a second-generation technique is adopted, i.e. Structural Equation Modelling (SEM), with the purpose of avoiding limitations associated with first-generation techniques. Applying SEM technique allows the researcher to simultaneously determine a series of inter-dependent linkages. All relationships proposed in the study proved to be significant. The findings of the study are helpful for the policy makers of the Textile sector.